2018
DOI: 10.1002/adv.22149
|View full text |Cite
|
Sign up to set email alerts
|

The role of synthetic P (MMA‐co‐MAH) as compatibilizer in the preparation of chlorinated polyethylene/polysodium acrylate water‐swelling rubber

Abstract: By multicomponent mechanical blending technology, water‐swelling rubber (WSR) was prepared through choosing chlorinated polyethylene (CPE), a superabsorbent polymer (cross‐linking poly(sodium acrylate), CPNaAA), and compatibilizer (poly(methyl methacrylate‐co‐maleic anhydride), P (MMA‐co‐MAH)) along with other minor additives. P (MMA‐co‐MAH) was synthesized by grafting maleic anhydride (MAH) onto methyl methacrylate (MMA). Microstructure, water‐absorbent properties, and mechanical properties of WSR were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…Thus, water absorption rates of the compositions were enhanced by high content of EVA or the presence of high filler concentration. Despite the high network densities, the present samples have exhibited higher water absorption rates compared to those earlier reported for chlorinated polyethylene filled with cross-linked poly (sodium acrylate) SAP in the presence of poly(methyl methacrylate-co-Maleic anhydride) compatibilizers [32] and PDMS-based polyuria which uses water for self-healing. [20]…”
Section: Water-swelling Degree Analysiscontrasting
confidence: 69%
See 2 more Smart Citations
“…Thus, water absorption rates of the compositions were enhanced by high content of EVA or the presence of high filler concentration. Despite the high network densities, the present samples have exhibited higher water absorption rates compared to those earlier reported for chlorinated polyethylene filled with cross-linked poly (sodium acrylate) SAP in the presence of poly(methyl methacrylate-co-Maleic anhydride) compatibilizers [32] and PDMS-based polyuria which uses water for self-healing. [20]…”
Section: Water-swelling Degree Analysiscontrasting
confidence: 69%
“…The water absorption rates of the various compounds at 1-7 days were computed by using the Equation (2) [32] ; SR 7 and SR eq represents the water-swelling ratio at 7 days and the equilibrium water-swelling respectively.…”
Section: Water-swelling Ratio and Volume Expansion Testmentioning
confidence: 99%
See 1 more Smart Citation
“…These results showed that MAH was grafted onto PEW. Compared to the FTIR spectrum of PEW- g -MAH, the FTIR spectrum of PEW- g -MAH-MMA ( Figure 2 b, Spectrum III) shows the peaks of the carbonyl groups in the five-membered anhydride ring at 1849 cm −1 and 1781 cm −1 , and an additional characteristic peak at 1731 cm −1 that can be attributed to the stretching vibration of the carbonyl groups on MMA [ 45 ]. It was observed that there was no absorption peak at 1637 cm −1 due to C=C vibrations, indicating that MAH and MMA were copolymerized and grafted onto the macromolecular chain of PEW.…”
Section: Resultsmentioning
confidence: 99%
“…Additional advantages are nontoxicity, high thermal and chemical resistance, and mechanical strength. These properties are used in such fields as medicine (lenses, dressings, and drug release), agrotechnics (water storage) and construction (waterproofing panels, fillers for fire‐retardant panes) . However, the problem here is that acrylate monomers are very sensitive to changes in environmental conditions.…”
Section: Introductionmentioning
confidence: 99%